2018
DOI: 10.1039/c7ob03012f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent incorporated sequential [3 + 2] annulation/substitution reaction of azomethine imines and propargyl sulfur ylide

Abstract: A novel solvent incorporated sequential [3 + 2] cycloaddition/substitution reaction of azomethine imines with propargyl sulfur ylide was developed. In the actual three-component reaction, propargyl sulfur ylide acts as a dipole reagent to furnish the annulation with azomethine imines, followed by the protic solvents acting as nucleophiles. The simple, mild, catalyst-free and practical protocol allows for the formation of N,N-bicyclic pyrazolidinones in moderate to excellent yields. Further transformation and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In 2018, Shen and Liang group reported a method for the synthesis of N,N-bicyclic pyrazolidinones 59 through a sequential [3 + 2] cyclization/intramolecular substitution reaction by using azomethine imines 58 and propargyl sulfonium salts 44 (Scheme 23). 36 The alcohol solvent served as the nucleophile, and a variety of N,N-bicyclic pyrazolidinones 59 were synthesized in moderate to excellent yields. The mechanism of this three-component reaction was postulated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In 2018, Shen and Liang group reported a method for the synthesis of N,N-bicyclic pyrazolidinones 59 through a sequential [3 + 2] cyclization/intramolecular substitution reaction by using azomethine imines 58 and propargyl sulfonium salts 44 (Scheme 23). 36 The alcohol solvent served as the nucleophile, and a variety of N,N-bicyclic pyrazolidinones 59 were synthesized in moderate to excellent yields. The mechanism of this three-component reaction was postulated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The versatile reactivities of N,N -cyclic azomethine imines have been consistently explored, allowing the facile construction of a variety of dinitrogen-fused heterocyclic systems. Thus, owing to their inherent dipolar character, a range of dipolarophiles including olefins [11], alkynes [12], enones [13], isocyanides [14], and allenes [15] were subjected to [3 + n] dipolar cyclization with N,N -cyclic azomethine imines to derive a range of fused dinitrogen-containing heterocycles. Interestingly, dimerization of N,N -cyclic azomethine imine under the UV-irradiation was observed by Rodina and Geissler et al, leading to the formation of a 1,5-diazabicycle [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, propargyl sulfonium salts can tautomerize to allenic sulfonium salts under basic conditions, including three reactive sites of α-carbon, β-carbon, and α′-carbon (Scheme ). As C 2 synthons, Kanematsu’s, Huang’s, , and our group reported that propargyl sulfonium salts involved [3 + 2] cascade annulation reactions to obtain related annulation products (structures A , B , C , and D in Scheme ). Propargyl sulfonium salts could react as a C 1 synthon via [5 + 1] annulation or both as a C 1 and C 2 synthon via the [4 + 1]/[3 + 2] annulation process to construct more complex scaffolds (structures E and F in Scheme ).…”
Section: Introductionmentioning
confidence: 99%